What readers thought about a research paper's approach to compare treatment effects on mortality. (17th August 2018) - Merino, José G; Loder, Elizabeth; Abbasi, Kamran
Abstract : What is the best way to compare treatment interventions when it is not evident which is standard and which is experimental? A research article on one approach generated a lively discussion of over 20 responses